Learning to Learn with Blended Learning - Natalia Andrejeva; Irina Ostroverkhaia (European Scientific Journal, ESJ, 2017)
This study investigates Blended Learning implementation into the challenging educational environment, characterized by limited time of faceto-face interaction of the teacher and the learners, and by an extrinsic motivation of the learners. The feedback elicited from the focus group of learners and the teacher has been analyzed using methods of systematization, calculation and description. The findings reveal that the positive features of Blended Learning appear to be relative ease of use; availability and accessibility of learning and teaching materials; achievement of certain learning and teaching goals; enhancement of learning strategies and learners’ self-organization; increase of learners’ autonomy and independence; inspirational nature of the learning content; growth of learners’ motivation; improvement of learners’ language competence. In summary, the most meaningful outcome of Blended Learning implementation proves to be the fact that the Blended Learning technology helps learners to learn how to learn: how to remember, review and recycle foreign words and collocations; how to plan the pieces of writing; how to use instructional, model and reference materials independently; how to search for information and find it; how to gain knowledge on their own; how to organize their own learning process; how to become responsible for their own education and development.